Managing Concussions in New Zealand Secondary Schools: Let's Take It Seriously - Skilton, Debbie; Zoellner, Anja; Badenhorst, Marelise; Mossman, Kate; Salmon, Danielle; Keung, Sierra; Thompson, Kylie; Lucas, Patricia; Walters, Simon; Sole, Gisela (Informa UK Limited, 2026)
INTRODUCTION: Concussion can cause lasting cognitive, physical, and emotional challenges, impacting academic performance. New Zealand secondary schools lack sufficient knowledge and resources to support affected students. We co-designed and implemented the Framework for Management of Concussion in New Zealand Secondary Schools (FRANCS). AIM: To explore experiences and perceptions of school stakeholders during 2 years of FRANCS implementation. METHODS: Sixty-nine participants from 12 schools (students, parents, staff, and healthcare providers) took part in semi-structured interviews or focus groups. Data were analyzed using framework analysis to identify themes. RESULTS: Four themes were developed: (1) Flexibility of implementation - friend or foe; (2) Owning the process; (3) The process is too onerous; and (4) External context and confounders. CONCLUSION: FRANCS' flexibility enabled some schools to adapt and integrate it into existing communication pathways, supporting students' return-to-learn. Others faced challenges, resource limitations, and low engagement. Effective implementation requires initial external support to tailor FRANCS to school contexts, establish communication and monitoring systems, and embed return-to-learn processes.
Keywords: Concussion; mild traumatic brain injury; qualitative methods; return-to-learn processes; secondary schools; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; Rehabilitation; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; 5203 Clinical and health psychology